Reduced Field-of-View Diffusion Imaging of the Human Spinal Cord: Comparison with Conventional Single-Shot Echo-Planar Imaging - Zaharchuk, G.; Saritas, E.U.; Andre, J.B.; Chin, C.T.; Rosenberg, J.; Brosnan, T.J.; Shankaranarayan, A.; Nishimura, D.G.; Fischbein, N.J. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: DWI of the spinal cord is challenging because of its small size and artifacts associated with the most commonly used clinical imaging method, SS-EPI. We evaluated the performance of rFOV spinal cord DWI and compared it with the routine fFOV SS-EPI in a clinical population. MATERIALS AND METHODS: Thirty-six clinical patients underwent 1.5T MR imaging examination that included rFOV SS-EPI DWI of the cervical spinal cord as well as 2 comparison diffusion sequences: fFOV SS-EPI DWI normalized for either image readout time (low-resolution fFOV) or spatial resolution (high-resolution fFOV). ADC maps were created and compared between the methods by using single-factor analysis of variance. Two neuroradiologists blinded to sequence type rated the 3 DWI methods, based on susceptibility artifacts, perceived spatial resolution, signal intensity–to-noise ratio, anatomic detail, and clinical utility. RESULTS: ADC values for the rFOV and both fFOV sequences were not statistically different (rFOV: 1.01 ± 0.18 × 10−3 mm2/s; low-resolution fFOV: 1.12 ± 0.22 × 10−3 mm2/s; high-resolution fFOV: 1.10 ± 0.21 × 10−3 mm2/s; F = 2.747, P > .05). The neuroradiologist reviewers rated the rFOV diffusion images superior in terms of all assessed measures (P < 0.0001). Particular improvements were noted in patients with metal hardware, degenerative disease, or both. CONCLUSIONS: rFOV DWI of the spinal cord overcomes many of the problems associated with conventional fFOV SS-EPI and is feasible in a clinical population. From a clinical standpoint, images were deemed superior to those created by using standard fFOV methods. ADCapparent diffusion coefficientAPanteroposteriorDTIdiffusion tensor imagingDWIdiffusion-weighted MR imagingEPIecho-planar imagingfFOVfull FOVHiReshigh resolutionisoDWIisotropic DWILoReslow resolutionRFradio frequencyrFOVreduced FOVROIregion of interestSNRsignal intensity to noise ratioSS-EPIsingle-shot EPISTIRshort tau inversion recoveryZOOM-EPIzonal oblique multisection EPI